Kontribusi peran perempuan pada usahatani padi ladang di Kecamatan Kulisusu Utara Kabupaten Buton Utara - Haerudin Tao; Sitti Rosmalah (Composite : Jurnal Ilmu Pertanian, 2023)
The time spent by women farmers in the research area is different in each stage of farming, especially field farming. Even the work placements for women farmers are often uneven and sometimes not in accordance with their skills and abilities. The purpose of the study was to determine the role of women farmers in farming, namely field rice in Tomoahi Village, North Kulisusu District, North Buton Regency. With a sample of 32 families from a population of 109 families, the sample was selected by simple random sampling. Sources of data through observation and questionnaires. The analysis technique is qualitatively and quantitatively then the results are assessed in the form of a percentage of each observed variable. The results showed that the women's work in farming activities was 1054.31 hours/farming, equivalent to 52.28%. The role of women farmers in upland rice farming in Tomoahi Village, North Kulisusu District, North Buton Regency is the largest in weeding activities with an outpouring of labor equivalent to 269.98 hours/farming and the smallest is in land processing activities of 0.03 hours/farming. Keywords: outpouring of time, field rice, peasant woman